CONSTRUCTION OF THE EXECUTION ARRANGEMENTS OF LABOR RELATIONS COURT DECISIONS ON TERMINATION OF EMPLOYMENT RELATIONS IN THE TOURISM ACCOMMODATION FIELD BASED ON LEGAL PROTECTION - Ryan Soma; I Nyoman Putu Budiartha; Johannes Ibrahim Kosasih (Warmadewa Press, 2024)
This means that there is no law, including the PPHI Law, which specifically regulates the execution of Labor Relations Dispute decisions. As a result, workers affected by layoffs are not guaranteed legal protection with regard to the application of Labor Relations Dispute Decisions (also known as PHI Decisions) in layoff disputes. Instead, it is currently unregulated (empty norms). Based on these conditions, the legal issues raised in this research are to analyze (1) the nature of the execution of PHI decisions in layoffs at Tourism Accommodation Companies; (2) The usefulness and legal certainty of executing PHI decisions for workers at Tourism Accommodation Companies; and (3) construction of arrangements for the execution of PHI decisions to offer defense against layoffs at lodging and tourism businesses. Normative legal research is the methodology employed in this study. The research findings indicate that (1) Ensuring the protection of workers' fundamental rights, as well as equal treatment and opportunity without discrimination based on any basis, is crucial to carrying out PHI decisions related to layoffs at tourism accommodation companies. This is done while keeping an eye on advancements and ensuring the welfare of workers and their families. the business world, especially the tourism accommodation business; (2) The usefulness and legal certainty of the execution of PHI decisions for workers at Tourism Accommodation Companies which have permanent legal force must be able to provide benefits for workers who have been laid off so that the decision does not cause unrest and chaos in the lives of people seeking justice, especially groups of workers who were laid-off. The execution of PHI decisions does not yet have legal certainty because the company as the defeated party generally does not carry out the contents of the decision voluntarily. Apart from that, the execution norms have not yet been regulated; and (3) Construction of arrangements for the execution of PHI decisions to provide legal protection in the layoff process at Tourism Accommodation Companies is carried out in accordance with Article 57 of the PPHI Law to complete the empty norms in the PPHI Law. The empty norms are due to Article 57 of the PPHI Law which refers to the absence of civil procedural law, especially regarding the execution of PHI decisions.